1998
DOI: 10.1074/jbc.273.47.31565
|View full text |Cite
|
Sign up to set email alerts
|

No Sliding during Homology Search by RecA Protein

Abstract: The RecA protein of Escherichia coli is a prototype of the RecA/Rad51 family of proteins that exist in virtually all the organisms. In a process called DNA synapsis, RecA first polymerizes onto a single-stranded DNA (ssDNA) molecule; the resulting RecA-ssDNA complex then searches for and binds to a double-stranded DNA (dsDNA) molecule containing the almost identical, or "homologous," sequence. The RecA-ssDNA complex thus can be envisioned as a sequence-specific binding entity. How does the complex search for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 49 publications
5
38
1
Order By: Relevance
“…Such dsDNA translocating activity has never been reported for the RecA/ hRad51 family of proteins. Correspondingly, it was shown that the search for homology promoted by RecA protein involves collision rather than extensive sliding of dsDNA (55). Our results indicate that hRad54 protein may drastically change the mechanism of homology search by promoting ATPase-dependent translocation of dsDNA along the filament.…”
Section: Human Rad54p Stimulates Hrad51p In the Presence Of Ca 2ϩmentioning
confidence: 72%
“…Such dsDNA translocating activity has never been reported for the RecA/ hRad51 family of proteins. Correspondingly, it was shown that the search for homology promoted by RecA protein involves collision rather than extensive sliding of dsDNA (55). Our results indicate that hRad54 protein may drastically change the mechanism of homology search by promoting ATPase-dependent translocation of dsDNA along the filament.…”
Section: Human Rad54p Stimulates Hrad51p In the Presence Of Ca 2ϩmentioning
confidence: 72%
“…Being completely disordered (27), the in vitro networks cannot, however, alter the dimensionality of the search (30). In contrast, the intracellular assemblies may promote a homology search by both an attenuated sampling volume that results from RecA-DNA coaggregation, and a reduced dimensionality which specifically stems from the longitudinal organization of the in vivo assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Single-molecule fluorescent measurements with a high spatiotemporal resolution were employed, which, in contrast to earlier experiments that indicated no sliding (35), have observed multiple diffusional events for RecA filaments on DNA. Using computer simulations, it was argued that sliding accelerates the homology search as much as 200 times (13).…”
Section: Introductionmentioning
confidence: 95%